Histological identification of Helicobacter pylori: comparison of staining methods. Issue 10 (1st October 2000) - Rotimi, O; Cairns, A; Gray, S; Moayyedi, P; Dixon, M F
Abstract : Aim —To determine whether two recently described staining methods (the modified McMullen's and the Helicobacter pylori silver stain HpSS methods) used for the histological identification of H pylori organisms are superior to two established techniques (the modified Giemsa and anti- H pylori antibody immunostain) in terms of availability, reproducibility, rapidity, sensitivity, and cost. Methods —Histological sections from 63 paired gastric biopsies from adult patients previously investigated for dyspepsia were stained with the four methods and these were assessed blindly and independently by two observers. Of the 63 patients, 30 were originally negative in all tests for H pylori infection, 30 were positive, and the remaining three cases had discordant results using a combination of five tests (rapid biopsy urease test, urea breath test, culture, serology, and histology). Results —Interobserver agreement was best with the antibody method (98%), followed by the McMullen's (90%), Giemsa (87%), and HpSS (85%). Of the 60 "gold standard" positive and negative cases, 30 were positive by the modified Giemsa stain, 29 by the McMullen's method, 29 by HpSS, and 30 by the antibody stain. However, there were two false positives with the HpSS method. The modified Giemsa is the cheapest and easiest to perform technically. Conclusions —When H pylori are present, careful examination will almost always reveal them, whichever of these stains is used. However, the modified Giemsa stain is the method of choice because it is sensitive, cheap, easy to perform, and reproducible.